(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Appeal against thedecision of the District Forum, State Commission and National Commission shouldbe presented before the State Commission, National Commission and SupremeCourt’ respectively within a period of thirty days from the date of verdict. The Supreme Court,National Commission and the State Commission may entertain an -appeal after theexpiry of the said period of thirty days if they are satisfied that there wassufficient cause for not filing it within that period.